2020
DOI: 10.5888/pcd17.200204
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for Keeping Parks and Green Space Accessible for Mental and Physical Health During COVID-19 and Other Pandemics

Abstract: The importance of engaging in any type of physical activity regularly, for both physical and mental health, is well established, and may be particularly beneficial in protecting the body and limiting the damage caused by the coronavirus disease 2019 (COVID-19). Exposure to nature or green space also has positive physical and mental health benefits. Closures of parks and green spaces during the COVID-19 pandemic has limited the options for physical activity and may affect vulnerable populations more than others… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
267
0
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 334 publications
(291 citation statements)
references
References 19 publications
11
267
0
13
Order By: Relevance
“…It is plausible that younger adults who typically work longer hours and earn less wage, are lacking both the time (e.g., due to long hours) and space (e.g., smaller dwelling) to meet physical activity goals. Outdoor activity could be a viable substitute [38], although this was not permitted in some countries during the pandemic [39]. Furthermore, increasing the number of repetitions performed during resistance training exercises can serve to adjust relative training intensity if lack of equipment is perceived as a barrier [40].…”
Section: Discussionmentioning
confidence: 99%
“…It is plausible that younger adults who typically work longer hours and earn less wage, are lacking both the time (e.g., due to long hours) and space (e.g., smaller dwelling) to meet physical activity goals. Outdoor activity could be a viable substitute [38], although this was not permitted in some countries during the pandemic [39]. Furthermore, increasing the number of repetitions performed during resistance training exercises can serve to adjust relative training intensity if lack of equipment is perceived as a barrier [40].…”
Section: Discussionmentioning
confidence: 99%
“…Under the closure of workplaces, schools, shopping malls, restaurants and other public places, the access of parks and open green spaces in the United States also got restricted by the policies. However, studies have been confirmed that these restrictions on parks and green spaces could possibly cause people severe physical and mental health issues especially those living in urban areas (Sallis and Pratt 2020; Slater et al 2020).…”
Section: Utilization Of Parks During the Covid-19 Pandemicmentioning
confidence: 99%
“…Activity-friendly environments and travel can play a significant role in the fight against COVID-19 given the established links between physical activity, improved immune defense and reduced vulnerability to COVID-19 infections [ 12 , 13 ]. At the same time, personalized protection in parks, public spaces and while biking is necessary to reduce the risks of clusters developing when outside crowding replaces inside crowding [ 14 ]. The size of public green spaces in cities clearly influences this risk [ 15 ].…”
Section: Commentarymentioning
confidence: 99%